2023
DOI: 10.1177/23821205231183878
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Learning Communities With Medical Students as Teachers

Abstract: In recent years, peer-assisted learning has emerged as a new and effective medical education modality. Near-peer tutoring utilizes a senior student serving as an instructor to a junior student. In 2019, the University of California, Irvine, School of Medicine (UCISOM) implemented a near-peer tutoring model beginning with first-year anatomy and physiology curricula. Following a successful pilot program, UCISOM launched a full-fledged near-peer tutoring program in 2020 named Collaborative Learning Communities (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Research has shown multiple interventions, such as mentoring, academic support, and students. However, the effectiveness of such interventions may be moderated by individual and contextual factors such as prior academic achievement, socioeconomic status, and institutional culture [48,49].…”
Section: Student Academic Performancementioning
confidence: 99%
“…Research has shown multiple interventions, such as mentoring, academic support, and students. However, the effectiveness of such interventions may be moderated by individual and contextual factors such as prior academic achievement, socioeconomic status, and institutional culture [48,49].…”
Section: Student Academic Performancementioning
confidence: 99%
“…The question arises whether CDs could have positive effects, such as improved collaboration, behavioral change, learning, or knowledge management [ 12 ]. There is some evidence that collaborative and peer-assisted learning can improve learning in the medical field [ 13 , 14 ] In pathology, especially digital slides have been shown to improve student learning and collaboration [ 14 – 17 ]. Surprisingly, a PubMed search for ‘collaborative document’ in August 2023 yielded only 15 hits.…”
Section: Introductionmentioning
confidence: 99%
“…The peer tutoring program entitled, Collaborative Learning Communities with Medical Students as Teachers (CLC-MSAT) program at UCISOM launched in 2019 and has successfully evolved to serve first through third year medical students 19 . As the team grew from a staff of 18 to 73 peer tutors in a four year period, our attention has also turned into cultivating future academic-oriented clinicians interested in exploring medical education as a career.…”
Section: Introductionmentioning
confidence: 99%